Pengaruh Inflasi, Investasi, dan Tingkat Upah Terhadap Tingkat Pengangguran di Bali - Sucitrawati, Ni Putu; Arka, Sudarsana (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2012)
Large populations can arise a problem, one of them is employment. Labor growth which faster than the growth of employment opportunities will increase the number of unemployment in the society. The development of tourism sector in Bali not made ??free of unemployment. This study discusses about effects of inflation, investment, and wages to the unemployment rate in the Bali province in 1998-2011 both simultaneously and partially. This study used multiple linear regression analysis techniques. The results of this study shows inflation, investment, and wages simultanously have significant effect on the rate of unemployment in Bali in 1998-2011. While partially, inflation and investment do not affect on the unemployment rate in Bali in 1998-2011. And wages partially have significant effect on the unemployment rate in Bali in 1998-2011.
Keywords: Unemployment; Inflation; Investment; Wage